Feasibility and Effectiveness of Speech Intervention Implemented with a Virtual Reality System in Children with Developmental Language Disorders: A Pilot Randomized Control Trial - Irene Cappadona; Augusto Ielo; Margherita La Fauci; Maria Tresoldi; Carmela Settimo; Maria Cristina De Cola; Rosalia Muratore; Carmela De Domenico; Marcella Di Cara; Francesco Corallo; Emanuela Tripodi; Caterina Impallomeni; et al. (MDPI AG, 2023)
Language disorders are characterized by impairments in verbal expression/understanding, including difficulties with one or more language components. The Virtual Reality Rehabilitation System (VRRS) is a bioelectromedical device equipped with exercise sections aimed at improving cognitive and language deficits. It also increases patient motivation and engagement. The aim of our study was to test the feasibility and efficacy of VRRS intervention to improve speech therapy treatment for children with speech disorders. Thirty-two patients were enrolled in this study and randomly assigned to the experimental (EG) or control group (CG). The CG underwent conventional speech therapy, while EG underwent VRRS-implemented speech therapy. Both groups were evaluated before (T0) and after (T1) the intervention using the Language Assessment Test. The results showed improvements in both groups. However, the EG group showed greater improvement in various areas, including comprehension of total words, repetition, naming of body parts, naming of everyday objects, total naming, morphosyntactic accuracy, sentence construction, average length of utterance, and spontaneous word production. This study demonstrated that VRRS can be a valuable tool for implementing effective speech rehabilitation. Further studies are needed, as the use of VRRS is still in its early stages, requiring larger samples sizes and long-term follow-up.